Synergy of Actors in Empowering Rice Farmers through Healthy Plant Management Program - Susi Pandan Sari; Isnaini Rodiyah (Universitas Muhammadiyah Sidoarjo, 2021)
The healthy plant management program in Kebalankulon Village is a program from Lamongan Regency which aims to empower rice farmers by applying organic fertilizers and medicines as a substitute for chemical fertilizers. In the healthy plant management program there are several actors involved, including the Lamongan Regency Agriculture Office, village government, and farming communities. This study aims to describe and analyze the synergy of actors in empowering rice farmers through a healthy crop management program, as well as the constraints on actor synergy in empowering rice farmers through a healthy plant management program. This research is a descriptive qualitative research with the technique of determining the informants using purposive sampling. The results of this study indicate that the synergy of actors in empowering rice farmers through a healthy plant management program in Kebalankulon Village, namely, first, coordination in planning related to healthy plant management carried out between the agricultural office and the village government to the farmer community already able to understand the mechanism of healthy plant management as an ingredient. discourse. However, coordination in implementing the village government is less able to provide assistance to farmers when fertilizing, due to the limited number of assistants in the field. Second, the communication carried out in the healthy plant management program is through socialization. Currently the socialization activities are not running because of the impact of the implementation of healthy plant management activities that are not running smoothly. Obstacles in the synergy between actors in empowering rice farmers through healthy plant management programs are the village government's lack of cooperation with other parties or the private sector to support facilities and infrastructure in healthy plant management, lack of village fund budgets for the implementation of healthy management programs, and adequate human resources. less competent in the implementation of healthy plant management in the field.